People of the streets - Parker, Tony. (London : Jonathan Cape, 1968)
what kind of lives they have, and what living them means...' First published in 1968, People of the Streets was Tony Parker's sixth book, for which he spent a year approaching and interviewing people in London who were living their daily lives on street corners, along gutters or in subways.
Keywords: London (England) -- Social conditions -- 20th century; Marginality, Social England London History 20th century